Debating the Inconsistencies between Constitutional Provisions on Decentralisation and Citizen Participation Realities in Zimbabwe (Journal of Governance and Development (JGD), 2014)
This paper provides a kaleidoscopic description and explanation on the challenges and problems associated with Zimbabwe’s governance terrain after the many years of political polarisation, economic crisis and social mistrust characterising the country. The present situation puts the whole debate of devolution as provided for in the new Constitution, to precariousness. The central thematic issues that this paper seeks to address are legality, constitutionality, and social, economic and spatial marginality that are likely to continue if the state remains stuck in erstwhile practices hence unwilling to move to redress that imbalances the characterise the nation today. This paper emanates from the fact that there is dearth of current literature in Zimbabwe on issues of decentralisation and constitutional issues. We use textual and discourse analyses to describe and explain this strands of debate in this present discussion. The article also adopts documentary review, where the Zimbabwean Constitution was assessed with the aim of exposing the intentions on devolution. From this study, it become clear that a big lacuna exists between constitutional intends and practice. The citizen participation notion is one that has not been implemented as the intensions on devolution have not been operationalised. The paper recommends political will on the part of the central government to implement the provisions of the New Constitution as a way of enhancing citizen participation, democratic governance and human rights promotion.